FRI0520 Improved patient-reported outcomes in psoriatic arthritis patients treated with abatacept: results from a phase iii trial. (15th June 2017) - Strand, V; Alemao, E; Lehman, T; Johnsen, A; Banerjee, S; Ahmad, H; Mease, P
Abstract : Background: In the Phase III ASTRAEA study (NCT01860976 ), abatacept (ABA) significantly increased ACR20 responses, with benefits on other musculoskeletal symptoms in patients (pts) with active psoriatic arthritis (PsA). 1 As PsA impacts HRQoL, assessing treatment (tmt) effect using patient-reported outcomes (PROs) is important. Objectives: To explore the effect of ABA tmt using PROs in intent-to-treat and post hoc analyses of ASTRAEA. Methods: Pts were randomized (1:1) to SC ABA 125 mg weekly or placebo (PBO) for 24 weeks (W). At W16, pts without ≥20% improvement in joint counts started open-label ABA. Adjusted mean changes from baseline (BL) to W16 (all pts) and W24 (responder analysis) in Short Form-36 (SF-36; physical and mental component summary [PCS, MCS] and individual domains using spydergrams), pain VAS and HAQ-DI scores, Dermatology QoL Index (DLQI) and FACIT-Fatigue scale (FACIT-F) were evaluated in the total population and subgroups stratified by BL CRP level and prior TNFi use. Proportions of pts reporting improvements ≥minimal clinically important difference (MCID) in SF-36 summary (≥2.5) and domain (≥5.0), FACIT-F (≥40) and HAQ-DI (<–0.22) scores and ≥normative values in SF-36 summary (≥50) and domains, FACIT-F (<40) and HAQ-DI (<0.5) at W16 were analysed in the total population. Results: In the total population, improvements in all PROs were numerically greater for ABA (n=213) vs PBO (n=211) at W16 and W24 and significant for SF-36 PCS at W16 and HAQ-DI at W24 (Table). At W16, improvements in all SF-36 domains were numerically greater with ABA, and significant for physical function, bodily pain and vitality. A higher proportion of pts receiving ABA vs PBO reported improvements ≥MCID in SF-36 PCS, MCS, SF-36 domains, FACIT-F, HAQ-DI (Fig) and DLQI (not shown) at W16. The proportion of pts whose scores were ≥normative values at W16 was higher with ABA vs PBO in SF-36 PCS, MCS, FACIT-F and HAQ-DI scores. At W24, improvements in SF-36 domain scores accrued in both groups, with numerical differences in favour of ABA except in social function. Improvements in PROs were greater with ABA tmt in BL CRP>upper limit of normal (ULN) vs CRP≤ULN and in TNFi-naïve vs -exposed subpopulations. Conclusions: Abatacept treatment improved many PROs in pts with active PsA, with larger benefits in the CRP>ULN and TNF-naïve subpopulations. References: Mease P, et al. Arthritis Rheumatol 2016;68(suppl 10): [Abstract 1041]. Disclosure of Interest: V. Strand Consultant for: AbbVie, Amgen Corporation, AstraZeneca, Biogen Idec, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Celltrion, Corrona, Crescendo/Myriad Genetics, EMD Serono, Genentech/Roche, GlaxoSmithKline, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sandoz, Sanofi, UCB, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, T. Lehman Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, A. Johnsen Employee of: Bristol-Myers Squibb, S. Banerjee Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, H. Ahmad Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, P. Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Novartis, Pfizer, Sun, UCB, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, Genentech, Janssen, Novartis, Pfizer, UCB